Весенние праздники, игры и забавы для детей - Петров Виктор Михайлович (Сфера, 1998)
Экземпляры: аб. (1998) / Инвентарный номер: 40611 / Цена: / Сис.шифр: 74.100.58 / Авт.знак: П 30 / ГРНТИ: 14.23 / ББК: 74.100.58